Menalar Secara Historis Misi Universal dalam Kitab Yunus - Junaydi Jufriadi Lempoy (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2022)
This research aims to reason historically the universal mission in the book of Jonah. The method used is a qualitative approach by analyzing the text of the Bible using historical criticism exegesis. Because this research is descriptive qualitative in nature without field research, the researcher as the main instrument utilizes literature studies with various literature ranging from printed books, journals, websites and online applications. After analyzing the introduction of the book of Jonah, the problematic interpretation of the book of Jonah, the universal mission contained in the book of Jonah, to reflecting on it theologically, the research results show that the book of Jonah can be reasoned with historically. The universal mission contained in one of the Old Testament books emphasizes the mission paradigm that cannot be confined by a particular group or nation. Then it becomes a challenge for thinkers and researchers who tend to emphasize ratios more to reflect on the possibility of reasoning historically about things that are considered nonsensical stories. Thus, it is highly recommended to conduct research on other books, both in the Old Testament and the New Testament to find universal missionary characteristics as well as to answer the challenges of the 21st century which are increasingly critical and crises.